A study on synthesis, optical properties and surface morphological of novel conjugated oligo-pyrazole films - Çetin, A.; Korkmaz, A.; Erdoğan, E.; Kösemen, A. (Elsevier Ltd, 2019)
The two novel pyrazole based organic semiconductor 2a, 2b were synthesized from reactions of 1H-pyrazole-3,4-dicarbonyl dichloride 1c and p-phenylene-diamine or o-phenylene-diamine. The structures of synthesized oligo-pyrazoles were characterized by 1H, 13C NMR, FT-IR, Gel Permission Chromatography (GPC). The novel oligo-pyrazole films were prepared from synthesized 2a, 2b and their thicknesses were found to be 84 and 220 ?m. The optical properties of films such as absorbance, transmittance and band gap (Eg) were determined by UV–vis spectroscopy. Two dimensional and three dimensional surface images of films produced on glass were obtained with Atomic Force Microscope (AFM). In the AFM results, the average roughness and the average surface roughness values were obtained as 40.44, 3.15 nm and 55.14, 7.91 nm for oligo-pyrazoles (2a) and (2b). Also, the skewness values and kurtosis values were obtained as 5.04, 131.73 and 0.75, ?8.49 for oligo-pyrazoles (2a) and (2b), respectively. Furthermore, the structures of the oligo-pyrazoles in the lowest energies were optimized by means of DFT calculation and their HOMO-LUMO orbitals were plotted. © 2018 Elsevier B.V.
Keywords: Absorbance; Conjugated polymer; Optical band gap; Organic semi-conductor; Pyrazole